Ion exchange membrane and preparation method thereof

By forming a sulfonated polyaniline layer on the surface of the base film of the ion exchange membrane, the problem of poor conductivity of the existing film is solved, and higher conductivity and mechanical strength are achieved, which is suitable for efficient applications of flow batteries.

CN119725593APending Publication Date: 2025-03-28ANHUI CONCH CLEAN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411828700.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing ion exchange membrane has poor conductivity, which limits its application in flow batteries.

Method used

The aniline polymer layer is introduced by in-situ polymerization on the surface of the base film, and combined with appropriate acids and initiators, a sulfonated polyaniline layer is formed to enhance the conductive properties and strength of the film.

Benefits of technology

It significantly improves the conductivity and voltage efficiency of the ion exchange membrane, while enhancing the thermal stability and mechanical strength of the membrane, and is suitable for efficient and stable operation of liquid flow batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725593A_ABST
    Figure CN119725593A_ABST
Patent Text Reader

Abstract

The invention discloses an ion exchange membrane and a preparation method thereof. The ion exchange membrane comprises a perfluorinated or non-fluorinated resin base membrane containing Lewis acid groups and an aniline polymer layer coated on the surface of the base membrane. The preparation method of the ion exchange membrane comprises the following steps: dissolving aniline and a silane coupling agent in an acidic aqueous solution to obtain a first solution; dissolving an initiator in an acidic aqueous solution to obtain a second solution; immersing a perfluorinated or non-fluorinated resin base membrane into the second solution, adding the first solution while stirring for reaction, and taking out the base membrane after the reaction to obtain an intermediate; and immersing the intermediate in fuming sulfuric acid for reaction, taking out and washing to obtain the ion exchange membrane. The conductivity of the ion exchange membrane is improved by introducing the polyaniline coating through in-situ polymerization, and the voltage efficiency of the battery is improved; on the other hand, the pore diameter of an ion channel is reduced, and vanadium ion penetrability is reduced. As the mechanical property of polyaniline is poor, the processability and thermal stability of polyaniline are improved through sulfonation reaction of polyaniline.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ion exchange membrane and a preparation method thereof, in particular to a composite ion exchange membrane and a preparation method thereof. Background Art

[0002] In the core structure of the advanced energy storage technology of flow battery, the ion conduction membrane plays a vital role. It is not only a natural barrier for the mutual penetration of vanadium ions in the positive and negative electrolytes, but also a key channel for the circulation of hydrogen ions and the formation of a closed loop of the battery. The performance of the ion conduction membrane is directly related to the overall efficiency and stability of the entire battery system. Therefore, the ideal ion conduction membrane should have high ion selectivity, excellent ion conduction efficiency, excellent chemical stability and economical and reasonable cost to meet the needs of efficient and stable operation of flow batteries.

[0003] At present, the dominant commercial membrane material in the market is perfluorosulfonic acid ion conductive membrane (Nafion). Although the membrane material has stable performance, its ion selectivity is insufficient and its cost is high, which to a certain extent restricts its widespread industrial application. In contrast, non-fluorine ion conductive membranes have significant advantages such as low cost, high thermal stability and mechanical strength, and show good ion selectivity. This type of membrane material achieves precise separation and effective transmission of conductive ions and protons through a fine pore size screening mechanism and charge repulsion effect. However, its relatively low conductivity is still a key factor restricting its further commercialization and large-scale application.

[0004] In order to improve the conductivity and vanadium ion barrier of the ion conduction membrane, Chinese patent CN101867050A discloses a composite proton exchange membrane, which is made by casting a film after mixing polyaniline and sulfonated polyetheretherketone solution and heteropolyacid. In this patent, although adding polyaniline to the membrane can improve the conductivity of the ion conduction membrane, the improvement of the conductivity of the membrane by polyaniline is relatively limited, and polyaniline depends on heteropolyacids such as phosphomolybdic acid and sulfonated polyetheretherketone to work. Once polyaniline is separated from the two and forms a polymer layer on the surface of the base membrane alone, its effect on improving the conductivity of the base membrane is relatively weak. Therefore, this patent must incorporate polyaniline in the de novo synthesis path of the membrane, and cannot use polyaniline to modify and transform the existing base membrane. The technical threshold is high and it is difficult to quickly industrialize and apply. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide an ion exchange membrane to solve the problem of poor conductivity of existing ion exchange membranes. Another purpose of the present invention is to propose a method for preparing an ion exchange membrane to solve the problem of how to prepare an ion exchange membrane.

[0006] Technical solution: The ion exchange membrane described in the present invention comprises a base membrane made of a perfluorinated or non-fluorinated resin material containing Lewis acidic groups and an aniline polymer layer coated on the surface of the base membrane.

[0007] Preferably, the perfluorinated or non-fluorinated resin material containing Lewis acidic groups includes one of perfluorinated sulfonic acid ion resin, sulfonated polyetheretherketone, sulfonated polyaryletherketone, sulfonated polysulfone, and sulfonated polystyrene.

[0008] Another aspect of the present invention discloses a method for preparing the above ion exchange membrane, comprising the following steps:

[0009] (1) dissolving aniline and a silane coupling agent in an acidic aqueous solution to obtain a first solution; dissolving an initiator in an acidic aqueous solution to obtain a second solution;

[0010] (2) immersing a perfluorinated or non-fluorinated resin base film in a second solution, and then adding the first solution to react under stirring, and after the reaction, taking out the base film to obtain an intermediate;

[0011] (3) The intermediate is immersed in fuming sulfuric acid for reaction, then taken out and washed to obtain an ion exchange membrane.

[0012] Preferably, in step (1), the silane coupling agent includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane, and the initiator includes at least one of potassium persulfate, ammonium persulfate, sodium persulfate and hydrogen peroxide.

[0013] Preferably, in step (1), the molar ratio of aniline: silane coupling agent: initiator is 0.1-2: 1-3: 0.01-0.05, and the ratio of the amount of aniline to the area of ​​the base film is 0.01-0.1 mL / cm 2 .

[0014] Preferably, in step (1), the acidic aqueous solution is an aqueous solution of at least one of sulfuric acid, nitric acid and hydrochloric acid, wherein H + The concentration is 0.1-1.0mol / L.

[0015] Preferably, in step (2), the volume ratio of the second solution to the first solution is 1-4:1-4, and the reaction conditions are -10-10°C for 0.25-4h.

[0016] Preferably, in step (3), the reaction conditions are room temperature for 1-3 hours.

[0017] Preferably, in step (3), the washing method is to use deionized water and ethanol to wash in sequence.

[0018] The present invention further applies the above ion exchange membrane to a liquid flow battery.

[0019] The liquid flow battery comprises at least one of an all-vanadium liquid flow battery, a zinc / bromine liquid flow battery, a zinc / iodine liquid flow battery, an iron / chromium liquid flow battery or a vanadium / bromine liquid flow battery.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0021] The present invention improves the conductivity of the ion exchange membrane and the voltage efficiency of the battery by introducing a polyaniline coating through in-situ polymerization; on the other hand, the pore size of the ion channel is reduced, which reduces the penetration of vanadium ions. Since the mechanical properties of polyaniline are poor, its processability and thermal stability are improved by sulfonating it. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a microstructure diagram of the ion exchange membrane prepared in Example 1. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0024] Example 1: An ion exchange membrane, such as Figure 1 As shown, it includes a base film made of a perfluororesin material containing Lewis acidic groups and an aniline polymer layer coated on the surface of the base film.

[0025] The preparation method of ion exchange membrane is as follows:

[0026] (1) dissolving aniline and vinyltrimethoxysilane in a 1M hydrochloric acid aqueous solution to obtain a first solution, wherein the final concentration of aniline is 1M, and the final concentration of vinyltrimethoxysilane is 1M; dissolving ammonium persulfate in a 1M hydrochloric acid aqueous solution to obtain a second solution at a final concentration of 0.03M;

[0027] (2) immersing the perfluororesin base membrane Nafion117 containing Lewis acidic groups into the second solution, and then dropping the first solution into the solution under stirring, reacting at 0° C. for 1 h, and taking out the base membrane after the reaction to obtain an intermediate; the volume ratio of the second solution to the first solution is 1:1;

[0028] (3) The intermediate is immersed in fuming sulfuric acid for sulfonation reaction at room temperature for 2 hours, then taken out and washed with deionized water and ethanol in turn to obtain an ion exchange membrane.

[0029] Example 2: The preparation method of the ion exchange membrane is as follows:

[0030] (1) dissolving aniline and γ-aminopropyltrimethoxysilane in a 0.3M sulfuric acid aqueous solution to obtain a first solution, wherein the final concentration of aniline is 1M and the final concentration of γ-aminopropyltrimethoxysilane is 3M; dissolving ammonium persulfate in a 0.3M sulfuric acid aqueous solution to obtain a second solution at a final concentration of 0.05M;

[0031] (2) immersing the perfluororesin base membrane Nafion117 containing Lewis acidic groups into the second solution, and then dropping the first solution into it under stirring, reacting at -10°C for 4 hours, and taking out the base membrane after the reaction to obtain an intermediate; the volume ratio of the second solution to the first solution is 1:4;

[0032] (3) The intermediate is immersed in fuming sulfuric acid for sulfonation reaction at room temperature for 1 hour, then taken out and washed with deionized water and ethanol in turn to obtain an ion exchange membrane.

[0033] Example 3: The preparation method of the ion exchange membrane is as follows:

[0034] (1) dissolving aniline and γ-methacryloxypropyltrimethoxysilane in a 0.1 M nitric acid aqueous solution to obtain a first solution, wherein the final concentration of aniline is 0.1 M, and the final concentration of γ-methacryloxypropyltrimethoxysilane is 1 M; dissolving hydrogen peroxide in a 0.1 M nitric acid aqueous solution to obtain a second solution at a final concentration of 0.01 M;

[0035] (2) immersing the sulfonated polyetheretherketone base membrane SPEEK-100 in the second solution, and then dropping the first solution into it under stirring, reacting at 10° C. for 0.25 h, and taking out the base membrane after the reaction to obtain an intermediate; the volume ratio of the second solution to the first solution is 4:1;

[0036] (3) The intermediate is immersed in fuming sulfuric acid for sulfonation reaction at room temperature for 3 hours, then taken out and washed with deionized water and ethanol in turn to obtain an ion exchange membrane.

[0037] Comparative Example 1: The preparation method of the ion exchange membrane is as follows:

[0038] The dipping solution was prepared by dissolving polyaniline with a molecular weight of 9500 in a 0.5M sulfuric acid aqueous solution at a final concentration of 0.05M;

[0039] Then, the perfluororesin base membrane was immersed in the dipping solution at 10° C. for 1 hour, the base membrane was taken out and immersed in deionized water for 2 hours, and then washed with deionized water and ethanol in turn to obtain an ion exchange membrane.

[0040] Comparative Example 2: The rest is the same as Example 1, except that:

[0041] Replace hydrochloric acid with phosphotungstic acid.

[0042] Comparative Example 3: The rest is the same as Example 1, except that:

[0043] The intermediate is not immersed in fuming sulfuric acid, but is directly washed to obtain the ion exchange membrane.

[0044] Comparative Example 4: The rest is the same as Example 1, except that:

[0045] The ammonium persulfate was replaced with potassium persulfate.

[0046] Comparative Example 5: The rest is the same as Example 1, except that:

[0047] The ammonium persulfate was replaced with sodium persulfate.

[0048] The ion exchange membranes prepared in Examples 1-3 and Comparative Examples 1-5 were tested for conductivity and strength, and all-vanadium redox flow batteries were assembled using these ion exchange membranes. The positive electrode electrolyte composition was VO 2 + / VO 2+ , the negative electrode electrolyte composition is V 3 + / V 2+ , the positive and negative electrodes are carbon felt, and the electrical properties of the battery are measured. The results are as follows:

[0049] Table 1 Test results of conductivity, strength and electrical properties of different ion exchange membranes

[0050]

[0051] As can be seen from the results in Table 1, the conductivity (voltage efficiency) and electrical properties of Comparative Examples 1, 2, 4, 5 and Nafion117 are lower than those of Example 1. Comparative Example 1 shows that it is difficult to improve the overall conductivity of the membrane by directly using polyaniline to prepare the polymer layer coated on the surface of the base membrane. Comparative Examples 2, 4, and 5 show that the types of acid and initiator also have a significant effect on the improvement of conductivity, and the effect mainly comes from the effect of acid and initiator on the structure of the polymer layer. The present invention forms a polyaniline layer in situ on the surface of the base membrane by combining appropriate acid and initiator with aniline monomer, which effectively improves the overall conductivity of the ion exchange membrane. The conductivity and electrical properties of Comparative Example 3 are comparable to those of Example 1, but the strength of the membrane is significantly lower than that of Example 1, indicating that the mechanical properties of the polyaniline layer are poor, and its preparation process will affect the strength of the base membrane, resulting in a significant reduction in the overall strength of the membrane. The present invention effectively improves the overall strength of the membrane by sulfonating the polyaniline layer, and the strength is significantly better than the existing Nafion117. The membrane strength of Comparative Example 1 is also significantly lower than that of Example 1, indicating that the direct use of polyaniline to prepare the modified layer will have a significant negative impact on the overall strength of the membrane. Although sulfonation reactions were performed in Comparative Examples 4 and 5 to strengthen the polymer modified layer, the structure of the polymer layer itself was loose and easy to fall off due to the selection of inappropriate initiators, and it was difficult to improve the overall strength of the membrane even after sulfonation reactions.

Claims

1. An ion exchange membrane, characterized in that: The invention comprises a base film made of a perfluorinated or non-fluorinated resin material containing Lewis acidic groups and an aniline polymer layer coated on the surface of the base film.

2. The ion exchange membrane according to claim 1, characterized in that: The perfluorinated or non-fluorinated resin material containing Lewis acidic groups includes one of perfluorinated sulfonic acid ion resin, sulfonated polyetheretherketone, sulfonated polyaryletherketone, sulfonated polysulfone and sulfonated polystyrene.

3. The method for preparing an ion exchange membrane according to claim 1 or 2, characterized in that: The steps include: (1) dissolving aniline and a silane coupling agent in an acidic aqueous solution to obtain a first solution; dissolving an initiator in an acidic aqueous solution to obtain a second solution; (2) immersing a perfluorinated or non-fluorinated resin base film in a second solution, and then adding the first solution to react under stirring, and after the reaction, taking out the base film to obtain an intermediate; (3) The intermediate is immersed in fuming sulfuric acid for reaction, then taken out and washed to obtain an ion exchange membrane.

4. The method for preparing an ion exchange membrane according to claim 3, characterized in that: In step (1), the silane coupling agent includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane, and the initiator includes at least one of potassium persulfate, ammonium persulfate, sodium persulfate and hydrogen peroxide.

5. The method for preparing an ion exchange membrane according to claim 3, characterized in that: In step (1), the molar ratio of aniline: silane coupling agent: initiator is 0.1-2: 1-3: 0.01-0.05, and the ratio of the amount of aniline to the area of ​​the base film is 0.01-0.1 mL / cm 2 .

6. The method for preparing an ion exchange membrane according to claim 3, characterized in that: In step (1), the acidic aqueous solution is an aqueous solution of at least one of sulfuric acid, nitric acid, and hydrochloric acid, wherein H + The concentration is 0.1-1.0mol / L.

7. The method for preparing an ion exchange membrane according to claim 3, characterized in that: In step (2), the volume ratio of the second solution to the first solution is 1-4:1-4, and the reaction conditions are -10-10°C for 0.25-4h.

8. The method for preparing an ion exchange membrane according to claim 3, characterized in that: In step (3), the reaction conditions are room temperature for 1-3 hours.

9. The method for preparing an ion exchange membrane according to claim 3, characterized in that: In step (3), the washing method is to use deionized water and ethanol to wash in sequence.

10. Use of the ion exchange membrane according to claim 1 or 2 in a liquid flow battery.

Citation Information

Patent Citations

  • Composite proton exchange membrane

    CN101867050A